Pengaruh Tarif dan Kualitas Pelayanan Kepuasan Penumpang pada Kapal Soby Star: The Influence of Tariffs and Service Quality of Passenger Satisfaction on Soby Star Ships - Ariwijaya, Heny; Lumayo, Indah (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2023)
This research was conducted to determine and analyze the effect of tariffs and service quality on passenger satisfaction on the Soby Star ship in North Bulagi District. Sampling used is purposive sampling. Samples were taken of 97 respondents, namely the community in North Bulagi sub-district. The data technique used multiple linear regression analysis, correlation coefficient (r), coefficient of determination (R2), F test and t test. The results of the regression analysis Y = 5.309 + 0.417XI + 0.226X2. Shows that tariffs and service quality simultaneously have a positive and significant effect on customer satisfaction (Y). The result of the correlation (r) of 0.590 shows that there is a very strong relationship between fares and service quality on passenger satisfaction. The coefficient of determination (R2) of 0.348 or 34.8 means that the magnitude of the influence of fares and service quality on passenger satisfaction and the remaining 65.2% is determined by variables outside the model being analyzed. Testing the hypothesis obtained that Fcount 25.035 > Ftable 3.09. This shows the meaning of Ho is rejected and Ha is accepted. The t-test of tariffs and service quality has a positive and significant effect on passenger satisfaction where (6.079 and 3.384) > ttable (1.985) and has a probability value of 0.000, and 0.001 <0.05